Water-sediment regulation drives multi-taxon biodiversity and ecological network dynamics in the Yellow River Estuary - Cheng-Rui Yan; Li-Sha Hu; Xiao-Min Zhang; Shao-Wen Li; Fan Li; Yun-Wei Dong (Regional Studies in Marine Science, 2025)

Research on Environmental Response Characteristic of Super-Long Inclined Shaft Tunnel and CO Diffusion and Ventilation Optimization of Blasting Procedures - Kong-fei Yu; Huai-bing Wang; Hong-yan Wang; Chen-qi Fan; Bu-rui Liu; Xuan-ke Ren (Applied Geophysics, 2025)

Photothermal modulation of the regenerative microenvironment for reversing optic nerve injury - Kexin Tan; Jiayu Wang; Qianyue Zhang; Shuo Wu; Haiyang Zhang; Yusha Liu; Zhaohan Qu; Siwei Liu; Rui Huang; Yan Liu; Yang Wang; Yingzhi Chen; et al. (Chemical Engineering Journal, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Recent research progress of methane dry reforming to syngas - Yan Wang; Rui Li; Chunyang Zeng; Wenjuan Sun; Hui Fan; Qingxiang Ma; Tian-Sheng Zhao (Fuel, 2025)

Multi-scale analysis of the influence of red-bed lithological interface on tunnel deformation and instability - Jing-Kai Qu; Yi-Guo Xue; Fan-Meng Kong; Cui-Ying Zhou; Zhen Liu; Zuo-Peng Wang; Jin-Rui Duan; Yan Ai; Zi-Ming Qu; Jian-Ning Wang; Bo Wang; Chao Lu; et al. (Engineering Geology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

Depletion of Albendazole and Its Metabolites and Their Impact on the Gut Microbial Community Following Multiple Oral Dosing in Yellow River Carp (Cyprinus carpio haematopterus) - Yue Liu; Yan Dai; Yan-Ni Zhang; Wen-Rui Wang; Yu-Xin Chen; Yang-Guang Jin; Long-Ji Sun; Shi-Hao Li; Fang Yang; Xing-Ping Li; Fan Yang (Fishes, 2025)
Healthy Yellow River carp (Cyprinus carpio haematopterus) reared at a water temperature of 23 ± 0.6 °C were orally administered albendazole (ABZ) at a dose of 12 mg/kg body weight (BW) once daily for seven consecutive days. At predetermined time points after the final administration, five fish were randomly selected for sampling. Plasma, skin-on-muscle, liver, and kidney tissues were collected, and the concentrations of ABZ and its three metabolites—albendazole sulfoxide (ABZSO), albendazole sulfone (ABZSO2), and albendazole-2-aminosulfone (ABZ-2-NH2−SO2)—were determined using high-performance liquid chromatography (HPLC). The results indicated that ABZ and ABZSO were widely distributed across tissues, while ABZSO2 and ABZ-2-NH2-SO2 were only present at trace levels. Pharmacokinetic analysis of ABZ and ABZSO in plasma and tissues was performed using noncompartmental analysis (NCA). ABZ peaked in plasma at 0.73 μg/mL at 24 h after the last administration, with an elimination half-life (t1/2λZ) of 38.56 h. ABZSO reached a peak plasma concentration of 1.54 μg/mL at 24 h, with a t1/2λZ of 53.73 h. According to China’s national standard, where ABZ-2-NH2−SO2 is the marker residue with a maximum residue limit (MRL) of 100 μg/kg in fish skin-on muscle, no withdrawal period was necessary. However, based on the European Union standard—which uses the sum of ABZ and its three metabolites as the marker residue and an MRL of 100 μg/kg in ruminants—a withdrawal period of 16 days (or 351 °C-days) was required. Additionally, the study assessed changes in the intestinal microbiota following multiple oral doses of ABZ. The results indicated that ABZ administration significantly altered microbial diversity and composition in a dose- and time-dependent manner. After drug withdrawal, the intestinal microbiota gradually returned to baseline levels, similar to the untreated control group.

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

“Iron -free” CdSe/ZnS quantum dots disrupt neural differentiation of embryonic stem cells via the induction of ferroptosis - Chen Chen; Rui Wang; Yutong Liu; Lifan Fan; Nanxin Ma; Qiqi Yan; Wenhao Wang; Zhihua Ren; Xia Ning; Tingting Ku (Environmental Pollution, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Bonenncarpas A–K: Coumarin derivatives with anti-inflammatory activity from Boenninghausenia sessilicarpa - Gang-Zhong Zhou; Ruo-Xi Hu; Qi-Jing Fan; Chu-Chu Xi; Yan-Gang Cao; Jia-Rui Li; Zheng-Yu Cao; Chun-Lei Zhang (Phytochemistry, 2025)

CYP321F3 mediates metabolic resistance to methoxyfenozide in rice stem borer, Chilo suppressalis - Fang-Rui Guo; Shu-Chao Wang; Yan Liu; Shuai Wang; Jing-Mei Huang; Hao Sun; Lin-Feng He; Yuan Xie; Song-Tao Qiao; Feng-Xia Yang; Chris Bass; Cong-Fen Gao; et al. (Pesticide Biochemistry and Physiology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Determination of five alternaria toxins in peppermint by dispersive solid-phase extraction coupled with ultra-high performance liquid chromatography-tandem mass spectrometry based on MOF-808-TFA - Minhai Liu; Yan Zhang; Rui Cheng; Ting Tan; Lan Guo; Fan Liu; Yiqun Wan (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Sodium-glucose cotransporter 2 inhibitors and contrast-induced nephropathy risk: a meta-analysis - Gang Fan; Lin Lin; Hong Zuo; Rui Yan; Chao Xu (European Journal of Clinical Pharmacology, 2025)

Prediction of sandstone porosity in coal seam roof based on variable mode decomposition and random forest method - Ya-ping Huang; Xue-mei Qi; Yan Cheng; Ling-ling Zhou; Jia-hao Yan; Fan-rui Huang (Applied Geophysics, 2025)

Highly electrostatic cellulose acetate materials assisted by copper ion coordination for air filtration - Ning Yan; Ting Gao; Li Hua; Fan Xie; Rui-Xin Liu; Ding-Gen Hu; Zhao-Qing Lu (Chemical Engineering Journal, 2025)

Graphene bilayer film responsive to ultraviolet, humidity, and temperature - Lin Wang; Tao Wang; Yalong Li; Yi Huang; Rui Li; Jing Zhang; Jie Jiang; Pei Li; Yan Fan; Liang Chen (Chemical Engineering Journal, 2025)

Design of a prismatic CERMET megawatt gas-cooled reactor(PC-MGCR) for deep space exploration - Yuhan Fan; Rui Yan; Guifeng Zhu; Liang Chen; Naiwen Zhang; Yang Zou (Annals of Nuclear Energy, 2025)

Microglia programmed cell death in neurodegenerative diseases and CNS injury - Ling Cai; Qiuyue Fan; Rui Pang; Chen Chen; Yueman Zhang; Haiyi Xie; Jingyi Huang; Yu Wang; Peiying Li; Dan Huang; Xia Jin; Yuxi Zhou; et al. (Apoptosis, 2025)

Effect of the Hofmeister series anion salts on the ice recrystallization inhibition activity of tamarind seed polysaccharide - Xianbao Sun; Shihao Dai; Rui Guo; Taijie Zhan; Fan Xie; Yuxing Kou; Xuan Ma; Yinan Chen; Lihua Song; Hui Zhang; Lu Ren; Chunmei Yuan; et al. (Food Hydrocolloids, 2025)

Identification and characterization of 16 tripartite motif-containing proteins from Takifugu obscurus - Li-Fan Cui; Rui Shen; Xiao-Rui Song; Yan Shi; Zhe Zhao; Ying Huang (Fish & Shellfish Immunology, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)